Strengthening Rattan Artisans’ Capacity Via BUMDes Berkat Mandiri Lamgaboh: (Lamgaboh Village, Lhoknga, Aceh Besar Case) - Siregar, Khairunnisa; Misbah, T. Lembong; Rusnawati, Rusnawati; Situmeang, Marini Kristina (Teunuleh Publisher, 2025)
This study aims to examine the form of collaboration and factors that affect the strengthening of the capacity of rattan craftsmen through the Village-Owned Enterprises (BUMDes) Berkat Mandiri program in Gampong Lamgaboh, Lhoknga District, Aceh Besar. The background of this research is based on the importance of economic empowerment of village communities through the development of local potential-based businesses. The main problem raised was the form of cooperation between BUMDes and rattan craftsmen, as well as the factors that support the success of the collaboration. This study uses a qualitative approach with a case study method. The data was collected through in-depth interviews with Keuchik, the Chairman of BUMDes, rattan MSME administrators, as well as five local artisans and traders. The results of the study show that real collaboration is established through the provision of raw materials, access to capital, joint production facilities, and promotional and marketing support. Supporting factors for the success of this collaboration include village government support, managerial capacity of BUMDes, active participation of artisans, and connectivity with external markets. The conclusion of this study is that the BUMDes Berkat Mandiri program is able to strengthen the economic capacity of rattan artisans in a sustainable manner through participatory collaboration and based on local needs.